The impact of external migration from rural areas on the labor force in the fields of agriculture, forestry and fisheries in Romania - Mihaela-Georgiana Oprea; Mihaela-Irma Vlǎdescu; Irina Băncescu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 12th Edition, 2021)
In the context of an increase in demand for labor in the European Union's internal market (where there is a regulatory framework allowing free movement of labor), particularly in areas such as agriculture, construction and domestic services, romanians' tendency to emigrate increases with the opportunity to earn higher income. Migration among rural working-age people has continued to increase, leading to an increase in labor shortages in particular in the fields of agriculture, forestry and fisheries. In this work, the link between the external rural exodus and the Romanian labor market is being analyzed in the fields of agriculture, forestry and fishing. The importance of this study derives from the fact that agriculture is one of the major branches of the national economy, which, due to the reduction in employment, loses its production potential. As a methodology we use Pearson correlation coefficient and descriptive spatial analysis to study the link between two variables: Number of temporary immigrants in working age (aged 15 to 64) in rural areas and the employed civil population in agriculture, forestry and fishing (at the NACE section level). Following the evolution of the employment in all three areas, a continuing downward trend is observed in the period analyzed from 2012 to 2019, while the number of working-age immigrants in rural areas is growing significantly. Given the current situation, the drop in the number of workers in the fields concerned deepens the disparities between rural and urban areas, jeopardizing Romania's food security.
Keywords: J01; J11; J43; O15; 330; force; agriculture; migration; rural